The Effects of Bovine Colostrum on the Stress-Hyperglycemia Ratio and the Triglyceride-Glucose Index in Exercise-Trained Healthy Subjects: A Double-Blind, Placebo-Controlled Clinical Study - Marwan Al-Nimer; Ahmed Al-Basri; Dinara Satmbekova; Ubaidilla DatKhayev (College of Pharmacy University of Baghdad, 2023)
Bovine colostrum (BC) is a natural substance that has been shown of benefits for exercising, and reducing the blood glucose levels in type 2 diabetes. Stress hyperglycemia is a brief rise in blood glucose levels caused by physiological stress. This placebo-controlled clinical study aimed to investigate the effects of BC on stress hyperglycemia and the triglyceride-glucose index in healthy subjects who trained in resistance exercise. This research was carried out at Al-Kut University College from April 30th to November 30th, 2022. Fifty healthy young men were randomly assigned: Group I (n = 24) received a placebo, whereas Group II (n = 26) received a 500mg single oral dosage of BC nutraceutical pill. During the treatment period, both groups of volunteers engaged in resistance exercise training. Body mass index (BMI), waist circumference (WC), stress glucose ratio (SGR), triglyceride-glucose index (TyGI), and rate pressure product (as a hemodynamic response) were all measured at the start and end of the eight-week study.‎ Stress blood glucose levels were considerably higher in Group II following resistance training (89.0±6.5 vs 102.1±11.5mg/dL, p<0.001), whereas stress HbA1c% did not alter (4.70±0.25 vs 4.66±0.29, p=0.608). Bovine colostrum significantly increases the SGR from 1.01±0.03 to 1.18±0.13, p<0.001. The TyGI at the stress glucose level was increased by 2.7%.  We conclude that bovine colostrum significantly elevates the stress hyperglycemic ratio without inducing significant changes in the TyGI following exercise. This impact is accompanied by a stabilizing hemodynamic response.